INDEKS KUALITAS TANAH PADA SATUAN LAHAN YANG DITANAMI JAGUNG DI KENAGARIAN MUNGKA, KABUPATEN LIMA PULUH KOTA - Fadil Hukama Hamdi; J Juniarti; A Agustian (Jurnal Tanah dan Sumberdaya Lahan, 2021)
Land continuously planted with corn will decrease land quality. Good land quality is needed to support soil function as a growing medium and keep a sustainable environment. This research was aimed to identify the soil quality index at land unit planted with corn in Mungka, ,Lima Puluh Kota Regency. This research used an explorative descriptive method through land survey and soil analyses in the laboratory. The samples were taken based on purposive random sampling at each land unit under the same slope (8%). There were three land units being sampled, and those were corn-corn, corn-eggplant, and corn-cassava cropping pattern. Corn-corn ropping pattern had the best soil quality index (0.89), followed by corn-cassava (0.86), and corn-eggplant (0.85) on the top 20 cm soil depth. On the 20-40 cm soil depth, the soil quality indices 0.82, 0.82, 0.83, for corn-eggplant, corn-corn, and corn-cassava cropping pattern, respectively. The quality index of the land under the corn cropping pattern was considered good either on the top 0-20 cm or 20-40 cm soil depth. This was due to the addition of organic matter from poultry manure to the land regularly. Based on this research, it is recommended to apply OM regularly to corn cropping pattern to keep a good soil quality index.